Turbulent transformation: abrupt societal disruption and climate resilient development. (3rd July 2021) - Schipper, E.L.F.; Eriksen, S.E.; Fernandez Carril, L.R.; Glavovic, B.C.; Shawoo, Z.
ABSTRACT: COVID-19 has triggered major upheavals to life as we know it in every corner of the planet. The governance response has been deep and far-reaching, albeit variable and contradictory. Disruptions like the pandemic inspire new perspectives on climate resilient development, especially with respect to the role of governance in navigating transformations. We reflect on what reactions and responses to COVID-19 around the world suggest about society's ability to transform – and what types of global development we need to transform away from – in order to support more climate resilient and equitable futures. We identify three key pivot points to stimulate further thinking on governance for climate resilient development: the tension between engendering transformation and returning back to normal; the role of disruption and uncertainty for triggering transformation; and the role of systemic inequality in how people are affected by crises. In particular, we spotlight the turbulent nature of transformation, and challenge the dominant belief that predicted, controlled and desired outcomes can be engineered through rational policy decisions. Climate resilient development navigates the turbulence of transformation through solidarity and socially equitable governance by opening up space for inclusive and even contestatory politics.